Activation of human endogenous retroviruses by Sox proteins induces cell apoptosis via the caspase-3 pathway - Hossain, Md. Jakir; Monde, Nami; Sasaki, Hiroyuki; Nyame, Perpetual; Amesimeku, Wright Andrews Ofotsu; Terasawa, Hiromi; Matsumura, Sojiro; Matsui, Takeshi; Tsutsuki, Hiroyasu; Maeda, Yosuke; Sawa, Tomohiro; Monde, Kazuaki (Frontiers in Microbiology, 2025)
Human endogenous retroviruses (HERVs) were domesticated millions of years ago as ancestral relics through germline infections and have become part of the human genome (8.3%). Over time, HERVs lost their innate ability to become virulent. We have previously reported that the transcription factor Sox2 is critical for human endogenous retrovirus-K (HERV-K) LTR5H activation and transposition in induced pluripotent stem cells. In the present study, we identified HERV-K LTR5H and LTR5B activation following Sox overexpression. In addition, we found that HERV-K Gag localized in the plasma membrane and that virus-like particles were released from Sox-expressing cells. Notably, a deformed nucleus was induced by cleaved caspase-3 in the HERV-K Gag-expressing cells. The caspase-3 inhibitors increased the number of HERV-K Gag-expressing cells by inhibiting the apoptotic pathway. Furthermore, retrotransposition of HERV-K was significantly enhanced in Sox2-expressing cells treated with caspase-3 inhibitors. Taken together, these results indicate that several Sox proteins increase HERV-K expression with cleaved caspase-3, suggesting that induction of the cell apoptotic pathway prevents genome impairment by HERV-K expression and retrotransposition.